2000
DOI: 10.1074/jbc.275.4.2455
|View full text |Cite
|
Sign up to set email alerts
|

β-Carbolines That Accumulate in Human Tissues May Serve a Protective Role against Oxidative Stress

Abstract: ␤-Carbolines are tricyclic nitrogen heterocycles formed in plants and animals as Maillard reaction products between amino acids and reducing sugars or aldehydes. They are being detected increasingly in human tissues, and their physiological roles need to be understood. Two ␤-carboline carboxylates have been reported to accumulate in the human eye lens. We report here on the identification of another ␤-carboline, namely 1-methyl-1-vinyl -2,3,4-trihydro-␤-carboline-3-carboxylic acid, in the lenses of some catara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 35 publications
3
71
0
Order By: Relevance
“…It is of interest that browning is markedly accelerated in dark brown and black brunescent cataracts, which may be due to the generation of singlet oxygen damage in these lenses. This would be consistent with the lower Trp levels in these lenses and the fact that several browning compounds isolated from dark brown cataracts are modi®ed Trp residues (Luthra et al, 1994;Pari et al, 2000).…”
Section: Discussionsupporting
confidence: 75%
“…It is of interest that browning is markedly accelerated in dark brown and black brunescent cataracts, which may be due to the generation of singlet oxygen damage in these lenses. This would be consistent with the lower Trp levels in these lenses and the fact that several browning compounds isolated from dark brown cataracts are modi®ed Trp residues (Luthra et al, 1994;Pari et al, 2000).…”
Section: Discussionsupporting
confidence: 75%
“…As mentioned above, harmaline inhibited the maximal production of oxidation product and therefore protected the apolipoprotein moiety against alteration. These results were in agreement with Pari et al (2000) who showed that -carbolines could quench singlet oxygen, superoxide and hydroxyl radicals and inhibit the oxidative formation of higher molecular weight aggregates of the test protein.…”
Section: Discussionsupporting
confidence: 92%
“…4). Despite the fact that they have been suggested as possible antioxidants [43], to the best of our knowledge there is no experimental (k t ) data for them. In aqueous solution, b-carbolines show an acid-base equilibrium with pK a around 7.…”
Section: Resultsmentioning
confidence: 96%